HEALTH EDUCATION THERAPEUTIC GROUP: SUPPORT FOR THE PROMOTION OF SELF-CARING AMONG USERS OF PSYCHO-ACTIVE SUBSTANCES - Selene Cordeiro Vasconcelos; Iracema da Silva Frazão; Vânia Pinheiro Ramos (Universidade Federal do Paraná, 2012)
This descriptive-exploratory study with a qualitative approach aimed to investigate the contributions of the Therapeutic Group 'Health Education in the Promotion of Self Care ' to eight psycho-active substance users under intensive treatment in a Psychosocial Care Center -Alcohol and Drugs (CAPSad) in the municipality of Recife in the state of Pernambuco. The data was collected between July and August 2011 by consulting patient records and interviews, which were recorded and submitted to thematic content analysis; the treatment and interpretation of the data was organized taking into account constructs from Dorothea Orem's Self-Care Theory. The contributions of the Therapeutic Group were identified as motivation for life, support for identifying therapeutic needs and construction of competencies for self-care. From the perspective of the users, this Group provides a therapeutic environment for health education through the exchange of knowledge between the participants, and support for acquiring healthy habits.